Hening Dalam Meditasi Sebagai Seni Kontemplasi Pikiran Harmonis - Made G. Juniartha; Ni Ketut Anjani (Maha Widya Duta : Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2021)
Life in the current era of globalization, various phenomena occurring in complex human life, make people look for various ways to get inner peace. This is a hope to be achieved in this world. So that various methods to achieve soul harmony are the top priority. Meditation is a condition of human consciousness in focusing the mind on the state of the body to consciously relax and the mind is allowed to be still, calm in balance, consciously wise to achieve ananda (happiness). Thought is a power that everyone can have. Mind is also the cause of humans to do something through the ten senses that are led, so that the mind is called Rajendriya. To practice meditation, someone is invited to control his thoughts. Mind control can be carried out with abhyasa vairagya in meditation, as a way of removing the five hindrances namely awidya, asmita, raga, dwesa, and abhiniwasa to attain a harmonious mind. This paper is adopted by the author to understand silence in meditation as the art of contemplating harmonious thoughts. This paper uses data collection methods consisting of observations and documents. The data analysis technique used is qualitative in nature with descriptive descriptions. The results of this paper show that by doing silence in meditation one can get a harmonious mind which has the characteristics of concentration, awareness, wisdom and love.Keywords: Silence; Meditation; The art of contemplation; Harmonious thoughts.